Stone wall prepared for sculpting bas-relief sculptures - 64 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in The photo gives a glimpse into how the stone was worked on to sculpt relief sculptures.